2017
DOI: 10.1007/s40888-016-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Bargaining agenda in a unionised monopoly with network effects: when corporate social responsibility may be welfare-reducing

Abstract: This paper investigates the bargaining agenda selection in a socially concerned unionised monopoly producing a network good. We show that the recently established result that under network effects the firm prefers sequential efficient bargaining may be reversed when there are social concerns. Thus, firm's social responsibility restores also in network industries the conventional result of the trade-union economics that the firm prefers right-to-manage (RTM). However, this may result rather paradoxical because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…where consumer surplus is We assume that firm 1 takes CSR strategy. That is, firm 1 is not only concerned with its own profits, but also with the consumer surplus and pollution damage (Fanti and Buccella, 2017, 2019Goering, 2012Goering, , 2014Lambertini and Tampieri, 2015;Ouchida, 2019;and others). Thus, the objective function of firm 1  is defined as:…”
Section: The Modelmentioning
confidence: 99%
“…where consumer surplus is We assume that firm 1 takes CSR strategy. That is, firm 1 is not only concerned with its own profits, but also with the consumer surplus and pollution damage (Fanti and Buccella, 2017, 2019Goering, 2012Goering, , 2014Lambertini and Tampieri, 2015;Ouchida, 2019;and others). Thus, the objective function of firm 1  is defined as:…”
Section: The Modelmentioning
confidence: 99%
“…On the side of network effects, the theoretical literature on network externalities has recently seen a renewed interest with contributions that re‐examined several existing models and changed some established results of the Industrial Organisation literature. For instance, (1) Hoernig (), Bhattacharjee and Pal (), and Chirco and Scrimitore () showed that the established results of the oligopoly managerial delegation literature may not hold, (2) Fanti and Buccella (, ) found that the common wisdom regarding the bargaining agenda (between unions and firms) and corporate social responsibility may change, (3) Song and Wang () showed that the strength of the network externality affects collusion between firms, which becomes more likely when products are close substitutes.…”
Section: Literature Review On Codetermination and Network Effectsmentioning
confidence: 99%
“…Assume that firm 1 engage in CSR activities. In other words, not only firm 1 concerns its profit, but it also concerns its consumers and the damage it causes to the environment (Goering, 2012(Goering, , 2014Fanti & Buccella, 2017, 2018Ouchida, 2019;Fukuda & Ouchida, 2020). Hence, firm 1's objective function can be described as:…”
Section: Methodsmentioning
confidence: 99%